2017
DOI: 10.21468/scipostphys.3.1.005
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Quantum Monte Carlo simulations of highly frustrated magnets: the frustrated spin-1/2 ladder

Abstract: Quantum Monte Carlo simulations provide one of the more powerful and versatile numerical approaches to condensed matter systems. However, their application to frustrated quantum spin models, in all relevant temperature regimes, is hamstrung by the infamous "sign problem." Here we exploit the fact that the sign problem is basis-dependent. Recent studies have shown that passing to a dimer (two-site) basis eliminates the sign problem completely for a fully frustrated spin model on the two-leg ladder. We generaliz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 101 publications
(213 reference statements)
10
48
0
Order By: Relevance
“…We initialized the algorithm at the identity matrix (which was randomly perturbed by a small amount). The phase diagram of the non-stoquasticity qualitatively agrees with the findings of (14), where the stochastic series expansion QMC method was studied. There, it was found that the sign problem can be completely eliminated for a completely frustrated arrangement where J × = J ∥ , while the sign problem remains present for partially frustrated couplings J × ≠ J ∥ .…”
Section: Easing In Practicesupporting
confidence: 82%
See 3 more Smart Citations
“…We initialized the algorithm at the identity matrix (which was randomly perturbed by a small amount). The phase diagram of the non-stoquasticity qualitatively agrees with the findings of (14), where the stochastic series expansion QMC method was studied. There, it was found that the sign problem can be completely eliminated for a completely frustrated arrangement where J × = J ∥ , while the sign problem remains present for partially frustrated couplings J × ≠ J ∥ .…”
Section: Easing In Practicesupporting
confidence: 82%
“…In an attempt to ease the sign problem of a given Hamiltonian, it is therefore natural to try and improve the average sign. For a few specific models, these improvements have been achieved by different means: For example, one can exploit known physics to find bases with improved average sign (14,22) that are often induced by sparse representations (17,23,24). For particular observables, one can also exploit clever decompositions of the Monte Carlo estimator into clusters with nonnegative sign (25)(26)(27)(28)(29)(30)(31).…”
Section: A Pragmatic Approach: Easing the Sign Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…The most notable example is the Marshall sign rule [2], eliminating the sign structure from the ground states of quantum antiferromagnets on bipartite lattices. The resulting theoretical insight means that new bases that simplify the sign structure for a specific frustrated magnet or fermion model are routinely discovered [3][4][5][6]. In turn, in a few instances it has also been rigorously proven that efficient transformations do not exist [7,8], rendering the sign structure "intrinsic."…”
Section: Introductionmentioning
confidence: 99%